Genome-wide association analyses identify SPOCK as a key novel gene underlying age at menarche. - Yao-Zhong Liu; Yan-Fang Guo; Liang Wang; Li-Jun Tan; Xiao-Gang Liu; Yu-Fang Pei; Han Yan; Dong-Hai Xiong; Fei-Yan Deng; Na Yu; Yin-Ping Zhang; Lei Zhang; et al. (PLoS Genetics, 2009)
For females, menarche is a most significant physiological event. Age at menarche (AAM) is a trait with high genetic determination and is associated with major complex diseases in women. However, specific genes for AAM variation are largely unknown. To identify genetic factors underlying AAM variation, a genome-wide association study (GWAS) examining about 380,000 SNPs was conducted in 477 Caucasian women. A follow-up replication study was performed to validate our major GWAS findings using two independent Caucasian cohorts with 854 siblings and 762 unrelated subjects, respectively, and one Chinese cohort of 1,387 unrelated subjects--all females. Our GWAS identified a novel gene, SPOCK (Sparc/Osteonectin, CWCV, and Kazal-like domains proteoglycan), which had seven SNPs associated with AAM with genome-wide false discovery rate (FDR) q<0.05. Six most significant SNPs of the gene were selected for validation in three independent replication cohorts. All of the six SNPs were replicated in at least one cohort. In particular, SNPs rs13357391 and rs1859345 were replicated both within and across different ethnic groups in all three cohorts, with p values of 5.09 x 10(-3) and 4.37 x 10(-3), respectively, in the Chinese cohort and combined p values (obtained by Fisher's method) of 5.19 x 10(-5) and 1.02 x 10(-4), respectively, in all three replication cohorts. Interestingly, SPOCK can inhibit activation of MMP-2 (matrix metalloproteinase-2), a key factor promoting endometrial menstrual breakdown and onset of menstrual bleeding. Our findings, together with the functional relevance, strongly supported that the SPOCK gene underlies variation of AAM.